2011
DOI: 10.1051/0004-6361/201015241
|View full text |Cite
|
Sign up to set email alerts
|

Multi-frequency VLBA study of the blazar S5 0716+714 during the active state in 2004

Abstract: Context. We study the jet kinematics of the blazar S5 0716+714 during its active state in 2003-2004 with multi-epoch VLBI observations.Aims. We present a kinematic analysis of the large-scale (0-12 mas) jet of 0716+714, based on the results of six epochs of VLBA monitoring at 5 GHz. Additionally, we compare kinematic results obtained with two imaging methods based on different deconvolution algorithms. Methods. The blazar 0716+714 has a diffuse large-scale jet, which is very faint compared with the bright comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Knots K1 and K3 move to the northeast along slightly different trajectories with apparent speeds of 18.1 ± 0.5 c and 21 ± 2 c, respectively. An apparent speed of ∼20 c seems to be common in the parsec scale jet of S5 0716+71 (see, e.g., Rastorgueva et al 2011). Knot K1 undergoes both an acceleration along the jet μ = 0.23 ± 0.06 mas yr −2 and perpendicular to the jet μ ⊥ = −0.19 ± 0.06 mas yr −2 .…”
Section: Radio Observationsmentioning
confidence: 99%
“…Knots K1 and K3 move to the northeast along slightly different trajectories with apparent speeds of 18.1 ± 0.5 c and 21 ± 2 c, respectively. An apparent speed of ∼20 c seems to be common in the parsec scale jet of S5 0716+71 (see, e.g., Rastorgueva et al 2011). Knot K1 undergoes both an acceleration along the jet μ = 0.23 ± 0.06 mas yr −2 and perpendicular to the jet μ ⊥ = −0.19 ± 0.06 mas yr −2 .…”
Section: Radio Observationsmentioning
confidence: 99%
“…Britzen et al (2009) suggest that there is an apparent stationarity of jet components relative to the core. However, recently apparent speeds of ∼40 c have been reported in Rastorgueva et al (2011), Larionov et al (2013), Lister et al (2013) and Rani et al (2015). Britzen et al (2009), Rastorgueva et al (2011) and Rani et al (2014) observed nonradial motion and wiggling component trajectories in the inner milliarcsecond jet region.…”
Section: Introductionmentioning
confidence: 97%
“…Owing to its remarkable variability, S5 0716+714 has been the subject of many optical monitoring campaigns (Wagner et al 1996;Montagni et al 2006;Rani et al 2011Rani et al , 2013Rani et al , 2015. Several authors carried out flux variability studies (e.g., Quirrenbach et al 1991;Wagner et al 1996) and morphological/kinematic studies at radio frequencies (Antonucci et al 1986;Witzel et al 1988;Jorstad et al 2001;Bach et al 2005;Rastorgueva et al 2011). The observed intraday variability at radio wavelengths is likely to be a mixture of intrinsic and external (due to interstellar scintillation) mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Britzen et al (2009) suggest that there is an apparent stationarity of jet components relative to the core; more recent studies, however, have reported motion as fast as ∼40 c (Rastorgueva et al 2011;Larionov et al 2013;Lister et al 2013). Non-radial motion and wiggling component trajectories have often been observed in the inner mas jet region of the source (Britzen et al 2009;Rastorgueva et al 2011;Rani et al 2014).…”
Section: Introductionmentioning
confidence: 99%